Strategy of development knrtu as a centre of training of innovative engineering personnel in the field of chemical technology - G. . Dyakonov; V. . Ivanov; V. . Kondratyev (Высшее образование в России)
The strategy of development of the Kazan national research technological university(KNRTU) for the next six years as Russian scientifically-educational center in the sphere of chemical technologies is considered. Mission, strategic targets and priorities are formulated, the realization stages and their tasks are marked out. The possibility of realization of the goalson the basis of the reached indicators and the results of the activities is substantiated. The conception of training of innovative engineers in the field of chemical technologies in KNRTU as the largest center of domestic technological education is offered. Lines of integration of engineering and social and economic education are presented.